Students’ physical activity in their daily life - Pocienė, Monika; Gedrimė, Lina; Jakubaitienė, Vanda; Morkūnienė, Rimantė (Slauga. Mokslas ir praktika, 2020)
Physical activity is one of the major factors of lifestyle strengthening physical capacity, health and wellbeing. Improving life conditions, technological advance make conditions for the individual to move less. Inactive student has lots of health problems, experiences inconvenience in his study process and becomes disabled and inactive employee in his professional and daily activities. It is important, therefore, to become physically active during the period of studies.The goal of the research: to assess physiotherapy students‘ physical activity in their daily life.Materials and methods: analysis of scientific literature, statistic and descriptive analysis.Results: 45 second-year physiotherapy students of Health Sciences faculty participated in the research. The main part of the respondents were the students of twenty, twenty- one year old and only a small part elder than 21 years old. The research was carried out under the permission of the head of KSC and following all principles of ethics. The participants who took part in the research were volunteers. The respondents were informed about the object and methods of it. Anonymity was guaranteed to them.Conclusions: Physical activity is the whole complex of active movements and actions which are performed by muscles and joints of certain intensity during a certain time. Physical activity improves physical and mental health, promotes blood circulation, metabolism and reduces the risk of developing various illnesses. Student‘s physical activity is high or moderate level of physical activity, as the students consume more than average of energy per week. The students, therefore, are physically active in their daily life. The students are engaged in moderate intensive physical work more often than in a very intensive physical activity.
Keywords: student; physical activity; physical load; health